Carbapenem-resistant Enterobacteriaceae (CRE) or Delayed Appropriate Therapy (DAT)—Does One Affect Outcomes More Than the Other Among Patients With Serious Infections Due to Enterobacteriaceae?. (4th October 2017) - Lodise, Thomas; Berger, Ariel; Altincatal, Arman; Wang, Rosa; Bhagnani, Tarun; Gillard, Patrick; Bonine, Nicole G
Abstract: Background: While CRE and DAT are both associated with worse outcomes, their relative impact to the clinical and economic burden among patients with infections due to Enterobacteriaceae is not well understood. This study assessed the independent and combined effect of these two items on selected outcomes among patients with these infections. Methods: Hospitalized adults between July 2011 and September 2014 were identified from Premier Hospital Database. Patients were diagnosed with complicated urinary tract infection, complicated intra-abdominal infection, hospital-associated pneumonia, or bloodstream infection, and had a positive culture for Enterobacteriaceae from a site consistent with infection type (date of culture draw was index date). Patients were required to receive antibiotics on this date or ≤2 days after. Delayed therapy was defined as no receipt of an antibiotic with microbiologic activity during this period. CRE was defined as resistant to ≥1 carbapenems. Inverse probability weighting and multivariate regression analyses were used to estimate the associations between CRE status, DAT and outcomes. Logistic models were used for composite mortality (in-hospital death or discharge to hospice), in-hospital mortality, and discharge to home (reference group was timely therapy plus non-CRE); generalized linear models, for post-index duration of antibiotic therapy, hospital length of stay (LOS), and costs. Results: A total of 50, 069 patients were included in the analyses; 514 had CRE and 16, 414 received DAT. A gradient effect was observed across strata as the burden of serious infections was least among the reference group, and greatest among patients with CRE infection who received DAT (Figure). For example, as compared with the reference group, the risk of composite mortality increased nearly fourfold in patients with CRE infection who received DAT; total in-hospital costs more than doubled. Conclusion: DAT has a stronger association than CRE on outcomes, and their effects are synergistic. Given these findings, better methods of early pathogen identification (especially organisms such as CRE) should reduce time to appropriate therapy, thereby improving outcomes in this patient population. Disclosures: T. Lodise, Allergan plc: Consultant, Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; A. Berger, Allergan plc: Consultant, Consulting fee; A. Altincatal, Evidera: Consultant, Salary; R. Wang, Evidera: Employee, Salary; T. Bhagnani, Allergan plc: Consultant, Consulting fee; P. Gillard, Allergan plc: Employee, Salary; N. G. Bonine, Allergan plc: Employee, Salary